Dynamic Mechanical, Dielectrical, and Rheological Analysis of Polyethylene Terephthalate/Carbon Nanotube Nanocomposites Prepared by Melt Processing - Juris Bitenieks; Remo Merijs Meri; Janis Zicans; Krisjanis Buks (International Journal of Polymer Science)
The polyethylene terephthalate/carbon nanotube (PET/CNT) nanocomposites were prepared by melt mixing using a twin screw extruder. CNT content was varied up to 5 wt. %. Morphology as well as dynamic mechanical, calorimetric, and rheological properties of the PET/CNT nanocomposites was investigated. Morphological studies indicated that CNT bundles are regularly distributed within the polymer matrix creating a connected network structure which significantly affects the nanocomposite properties. Dynamic mechanical thermal analysis revealed increase in storage and loss modules of the investigated PET nanocomposites by increasing the content of CNTs. Differential scanning calorimetry results demonstrated increase in crystallinity of the investigated PET nanocomposites upon addition of the nanofiller. Rheological studies demonstrated that CNT addition up to 5 wt. % caused increment in complex viscosity and storage modulus. Rheological percolation threshold was observed to be 0.83 wt. % of CNT concentration, respectively.